A wearable UHF RFID tag antenna-based metamaterial for biomedical applications - Abdelhadi Ennajih; Badr Nasiri; Jamal Zbitou; Ahmed Errkik; Mohamed Latrach (Bulletin of Electrical Engineering and Informatics, 2020)
The development of miniature antennas for bio-medical applications has attracted the attention of many researchers in the last years. In this letter, we provide a miniature antenna for the RFID tag for identifying patients in African and European hospitals. The proposed antenna is designed on a flexible silicon substrate with a relative dielectric constant of 11.9 and a thickness of 1.6mm. An in-depth study of the proposed wearable antenna was made in free space and on human tissue. The achieved results showed good performance in terms of miniaturization, bandwidth, impedance matching and, reading distance. The presented tag antenna is designed and simulated by using CST-MWS solver and the results were validated by HFSS and both results are in good agreement.